(untitled) (Health Renaissance, 2016)
Tuberculosis is one of the major public health problems in South-East Asian countries with immense socio-economic impacts. The advantage and disadvantage of starting anti-tubercular therapy in presumptive diagnosis of pulmonary tuberculosis is debatable in a resource constrained settings. Even in the face of high prevalence, important pitfalls warrant consideration. Health Renaissance 2014;12(3): 224-226